Blue hydrogen: Current status and future technologies - AlHumaidan, Faisal S.; Absi Halabi, Mamun; Rana, Mohan S.; Vinoba, Mari (Energy conversion and management, 2023)
[Display omitted] •Significant transition is expected in world energy system over the next 30 years.•Inclusion of blue hydrogen is inevitable for the transition toward hydrogen economy.•Oxygen-based processes are most efficient for greenfield blue hydrogen applications.•Carbon intensity and thermal efficiency are crucial factors in blue H2 technologies.•Mature carbon capture technologies can remove 95% of CO2 in blue H2 production. Hydrogen is expected to play a key role in the world’s energy-mix in the near future within the context of a new energy transition that has been ongoing over the past decade. This energy transition is aiming for hydrogen to meet 10–18% of total world energy demand by 2050. However, such a transition requires addressing numerous technological and economic challenges in the complete value chain: production, storage, transport, distribution, and application. This energy transition is backed by policies and roadmaps by many countries of high energy consumption, as well as many companies that cover the complete value chain. The transition targets green hydrogen as a priority, which may happen if electrolysis technologies significantly advance. However, blue hydrogen, produced from fossil fuels with CO2 capture, is currently viewed as the bridge between the high-emission grey hydrogen and the limited-scale zero-emission green hydrogen. This review highlights the features of different commercially deployed and new emerging hydrogen production processes from fossil fuels and biofuels, along with the recent advancements in hydrogen storage and transport. The review also reports the status of latest key developments in carbon capture technologies, which are critical for blue hydrogen production. The paper also critically reviews the costs and the carbon footprints of emerging technologies, identifies the requirements to attain large-scale production for commercialization, and provides background information for the fossil fuels industry to be an active player in the current energy transition. The techno-economical assessment of many recent studies has indicated that the oxygen-based system, such as auto-thermal reforming and partial oxidation, is the most efficient for producing greenfield blue hydrogen.